NARRATIVE ANALYSIS: EXPLORING THE POWER DYNAMIC OF RURAL HOUSEWIVES WHOM ARE ALSO FARM WORKERS - Kezia Dewi Fortuna, Dominica; Dwiningtyas Sulistyani, Hapsari; Bayu Widagdo, Muhammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study explores the power dynamics of rural housewives who also work as farm laborers. The main focus of the study is to understand their autonomy and decisionmaking position within the household context. Using a qualitative approach, this research involved in-depth interviews and participant observation of a number of housewives in rural areas. The key findings reveal that these housewives generally lack significant personal autonomy within their households. This is largely due to their limited understanding of gender equality concepts and their right to participate in household decision-making. As a result, they tend to choose passivity and submission to their husbands' authority. This study highlights the importance of education on gender equality and women's empowerment in rural areas. The implications of these findings indicate a need for programs that can increase awareness and understanding among housewives about their rights, as well as encourage more active participation in household decision-making.